Luminescent Assay for the Screening of SARS‐CoV‐2 MPro Inhibitors. (14th June 2022) - Sondag, Daan; Merx, Jona; Rossing, Emiel; Boltje, Thomas J.; Löwik, Dennis W. P. M.; Nelissen, Frank H. T.; van Geffen, Mark; van 't Veer, Cornelis; van Heerde, Waander L.; Rutjes, Floris P. J. T.
Abstract: Since the outbreak of SARS‐CoV‐2 in December 2019 millions of infections have been reported globally. The viral chymotrypsin‐like main protease (M Pro ) exhibits a crucial role in viral replication and represents a relevant target for antiviral drug development. In order to screen potential M Pro inhibitors we developed a luminescent assay using a peptide based probe containing a cleavage site specific for M Pro . This assay was validated showing IC50 values similar to those reported in the literature for known M Pro inhibitors and can be used to screen new inhibitors. Abstract : A luminescent assay for the main protease M Pro of SARS‐CoV‐2 was developed and subsequently used for the screening of inhibitors of the chymotrypsin‐like protease. The caged luminescent peptide probe used in this study releases photons upon proteolytic activity of M Pro in the presence of luciferase.